Cattle service with drugs - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1986)
Prophylactic drugs are helping cattle in Tanzania to survive under tsetse conditions In a two-year trial, 95 Boran cattle calves were split into three groups. One group of 37 calves was treated with the drug isometamidium chloride (Samorin) every...